2021
DOI: 10.3390/ijerph18189654
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Motivation among Key Populations to Engage with Tuberculosis Screening and Testing Services in Northwest Tanzania: A Mixed-Methods Analysis

Abstract: In northwest Tanzania, many artisanal small-scale miners (ASMs) and female sex workers (FSWs) live in informal communities surrounding mines where tuberculosis (TB) is highly prevalent. An active case finding (ACF) intervention to increase TB case notification was undertaken in two districts. Alongside this, a study was implemented to understand engagement with the intervention through: (1) quantitative questionnaires to 128 ASMs and FSWs, who either engaged or did not engage in the ACF intervention, to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…For a long time, artisanal miners have been blamed for their seemingly poor healthseeking behaviour [12,43]. Contrary to this view, a growing body of evidence from southern Africa shows that this is not the case [38,44,45]. Our findings are consistent with this growing body of evidence as we observed that almost all ASMs are keen on having regular screenings for HIV, TB, and silicosis, while those who get sick are willing to seek medical care.…”
Section: Discussionsupporting
confidence: 85%
“…For a long time, artisanal miners have been blamed for their seemingly poor healthseeking behaviour [12,43]. Contrary to this view, a growing body of evidence from southern Africa shows that this is not the case [38,44,45]. Our findings are consistent with this growing body of evidence as we observed that almost all ASMs are keen on having regular screenings for HIV, TB, and silicosis, while those who get sick are willing to seek medical care.…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies demonstrated that ionizing radiation led to increased DNA damage and chromosome aberrations after standard dose chest CT, whereas no such effect was observed for low-dose CT. 11 Therefore, various approaches have been examined for the reduction of radiation dose without a loss in diagnostic accuracy. Among other efforts, reduced slice imaging, 5 low radiation dose imaging, 12 and the use of magnetic resonance imaging 13,14 have been evaluated for the assessment of lung parenchyma alterations in SSc patients. So far, these efforts have been accompanied by a loss of accuracy.…”
mentioning
confidence: 99%
“…Therefore, various approaches have been examined for the reduction of radiation dose without a loss in diagnostic accuracy. Among other efforts, reduced slice imaging, 5 low radiation dose imaging, 12 and the use of magnetic resonance imaging 13,14 have been evaluated for the assessment of lung parenchyma alterations in SSc patients. So far, these efforts have been accompanied by a loss of accuracy 15 .…”
mentioning
confidence: 99%